Sistem Pendukung Keputusan Penerima Beasiswa PPA Dan BBM Menggunakan Metode Simple Additive Weighting (SAW) - M. Safii (STIKOM Tunas Bangsa Pematangsiantar, 2017)
Improving Academic Achievement Scholarship (PPA) and Student Learning Aid (BBM) is one of the stimulus given to the government for students with the aim of motivating students to enhance the spirit of learning. In accordance with the program guidelines issued by the Directorate General of Higher Education must follow the principle of 3T is Right Target, Right Number and Timely. Computer Informatic Management Academy (AMIK) Tunas Bangsa Pematangsiantar is one of the private universities obtained on the scholarship quota. In accordance with the number of students currently as many as 1,400 people then the allocation of the scholarship must be selected carefully to fit the government guidelines. In this case we need a method that can support decision boosters system (DSS) in determining the grantee is using simple additive weighting method (SAW). With the basic concepts seek a weighted sum of the rating performance of each alternative on all attributes that require a decision matrix normalization process. This method can make an assessment criteria and detailed compound with a comprehensive framework considerations hierarchy process which then calculate the weights to each criterion in determining the priority recommendations of PPA and BBM scholarship recipients in accordance with the target.